Face Descry System in Exams Committees - Ahmed, Eman A.E. (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The main objective of the proposed face descry system is to use the face in the exams committees as a password to authenticate the students during exams periods. In such places, more security is needed than only the existing of the person. Different applications for this work can be applied for example, authentication for the persons using their faces in front of ATM instead of using password and Person verification for self-serviced clearance using E-passport is another important typical application. All these application can be considered as cooperative user scenarios in which the user is willing to be cooperative by presenting his/her face in a proper way (for example, in a frontal pose with neutral expression and eyes open) in order to be granted the access or privilege. Face recognition has several advantages over other biometric modalities such as fingerprint and iris: besides being natural and nonintrusive, the most important advantage of face is that it can be captured at a distance and in a covert manner. In this paper, face recognition is used to face verification (or authentication) which involves a one-to-one match that compares a query face image against an enrollment face image whose identity is being claimed. The proposed system consists of four phases. The first phase is the pre-processing phase. The second phase is the face detection based on Viola-Jones method. The third phase is the proposed Moving Average Window conversion. The last phase is the face verification phase, in this phase the similarity between the query face image and the enrollment face image whose identity is being claimed is calculated and the decision is taken depending on two classification parameters (Structural Similarity Measure (SSIM) and Color Measurement Committee (CMC) distance. The experimental results were viewed and compared.